PENGARUH KETERAMPILAN GURU DALAM MEMBERIKAN PENGUATAN PADA PEMBELAJARAN PAI TERHADAP PARTISIPASI AKTIF PESERTA DIDIK DI SMPN 3 SINJAI UTARA - Desianti, Nurfadillah; Suriyati, Suriyati; Nur, Makmur Jaya (STAI YAPIS Takalar, 2023)
This study aims to prove the effect of the teacher's skills in providing reinforcement in PAI learning on the active participation of students at SMPN 3 Sinjai Utara. This research is a quantitative research using a survey approach. Data taken using questionnaires and documents. Data processing uses multiple regression analysis techniques with a significant level of 95% using SPSS 20. This study shows that the skills of teachers in providing reinforcement significantly influence the active participation of students in Islamic Religious Education subjects at SMPN 3 Sinjai. Whereas at a significant value or probability of 0.000 <0.05, the teacher's skills in providing reinforcement have an influence on the active participation of students in Islamic Religious Education subjects at SMPN 3 Sinjai.2). The great influence of the teacher's skills in providing reinforcement to the active participation of students in the subject of Islamic Religious Education at SMPN 3 Sinjai can be seen in the model summary table by looking at R Square = 0.641 or 64.1% so the teacher's skills influence in providing reinforcement to active participation students in the subject of Islamic Religious Education at SMPN 3 Sinjai is 64.1%, the rest is influenced by other factors